The Female Circumcision Controversy - Gui Joya Jafri (International Institute of Islamic Thought, 2002)
Female circumcision is a highly contested "tradition" practiced in many parts of the world, particularly Africa. International human rights campaigns refer to the practice as "female genital mutilation" (FGM) and seek to eliminate it; its practitioners tend to defend it even after it has been declared illegal. Within this charged environment, Ellen Gruenbaum has undertaken the difficult task of examining the controversy from a more culturally sensitive perspective based on her years of fieldwork in Sudan.